Assessing pulmonary circulation in severe bronchopulmonary dysplasia using functional echocardiography. Issue 1 (5th January 2021) - Sehgal, Arvind; Blank, Douglas; Roberts, Calum T.; Menahem, Samuel; Hooper, Stuart B.
Abstract: Pulmonary hypertension (PH) is common in infants with severe bronchopulmonary dysplasia (BPD) and increases the risk of death. The objectives of this preliminary study were to compare responses of pulmonary circulation parameters to 100% oxygen (O2 ) and inhaled nitric oxide (iNO) in infants with BPD and PH using echocardiography. Responses between fetal growth restriction (FGR) and appropriate for gestational age infants were compared. Ten infants <28 weeks GA at birth were assessed at ≥36 weeks corrected gestation. Baseline echocardiography1 was performed which was repeated (echocardiography2) after 30 minutes of O2 . After a gap of 2–3 hours, iNO was administered for 15 minutes and echocardiography3 was performed, followed by iNO weaning. The gestation and birthweight of the cohort were 25.9 ± 1.6 weeks and 612 ± 175 g. Assessments were performed at 38.7 ± 1.4 weeks corrected gestational age. Baseline time to peak velocity: right ventricular ejection time (TPV/RVETc) increased from 0.24 ± 0.02 to 0.27 ± 0.02 (O2, p = .01) and 0.31 ± 0.03 (iNO, p < .001), indicating a decrease in pulmonary vascular resistance [PVR]. Baseline tricuspid annular plane systolic excursion (TAPSE) increased from 8.1 ± 0.6 mm to 9.3 ± 0.7 mm (O2, p = .01) and 10.5 ± 1.1 mm (iNO, p = .0004), indicating improved ventricular systolic performance. Percentage change for all parameters was greater with iNO. Significant correlations between cardiac performance and PVR were noted. FGR infants noted higher baseline PVR (TPV/RVETc, 0.21 ± 0.02 vs. 0.25 ± 0.01, p = .002), lower ventricular performance (TAPSE, 7 ± 1.2 mm vs. 8.6 ± 6 mm, p = .003), and lower percentage change with O2 and iNO. A reactive component of pulmonary circulation provides real‐time physiological information, which could rationalize treatment decisions. Abstract : Pulmonary vasoreactivity testing with oxygen and inhaled nitric oxide can be performed with echocardiography monitoring. Flow through a patent ductus arteriosus portrays sudden hemodynamic shifts, indicating a reactive pulmonary circulation.